Forward osmosis and electro kinetic power generation : achieving consistent water flux rate - Loh, Wei Long. (2013)
A novel energy generation method coupling the effect of Forward osmosis (FO) and electro kinetic (EK) system has been proposed. Henceforth, for a more realistic representation of the system a continuous set up has to be established. A continuous set up is largely dependent on the forward osmosis process. The existence of the phenomenon of dilutive external concentration polarization has been illustrated in this study as the main obstacles in preventing the establishment of such set up. To mitigate or reduce the effect of the dilutive ECP, the investigation of different parameters and their effect on the water flux rate has been investigated. Parameter such as different method of cross flow, cross flow rate, draw solution concentration has been investigated. Investigation has look into possible reason on the limitation of the current FO module in establishment of such continuous system. A new design with feature intended to support the continuous set up has been proposed. Lastly, recommendation for further improvement or add on to the new design and investigation into other means of improving the process has been proposed.